Computational study of microparticle effect on self-propelled jumping of droplets from superhydrophobic substrates. (October 2017) - Farokhirad, Samaneh; Lee, Taehun
Abstract : Hihglights: Coalescence-induced jumping of a single-particle-laden droplet from superhydrophobic substrates was simulated using a multiphase lattice Boltzmann method. To the best of our knowledge, this is the first numerical work to account for the effect of a particle presence on the self-propelled jumping of droplets from superhydrophobic substrates. A neutrally wetting particle immersed in the interface of the droplet and air promotes the vertical jumping distance, compared to a particle-free droplet. Increasing the size of a partially immersed particle enhances the jumping velocity which carries the particle to a sufficient distance from the substrate. When a partially immersed particle is placed at the interface and near to the non-wetting substrate, it boosts the jumping velocity of the droplet. Abstract: We present three-dimensional numerical simulations, employing a lattice Boltzmann method for three-phase system of liquid, gas, and solid, and investigate the influence of a solid particle on the dynamic and departure of a droplet after coalescence on superhydrophobic substrates. A particle can be removed autonomously by the jumping motion of the droplet, which partially or fully covers the particle. This spontaneous removal from superhydrophobic substrates is achieved by converting surface energy to kinetic energy, independent of gravity. We discussed the effect of size, wettability and initial placement of particle on the evolution of lateral and vertical motion of the droplet. The results indicate that the droplet with a fully immersed particle, as in the floating mechanism, reaches to the same equilibrium height as a particle-free droplet. However, the droplet with a partially immersed particle, as in the lifting mechanism, can have a substantial jumping velocity compared to a particle-free droplet. As the size of the partially immersed particle approaches its critical limit, which is equal to the size of the droplet, the droplet jumping and transport from the substrate is enhanced. Besides the particle size, the particle wettability can result in a considerable droplet jumping velocity. A particle with a neutrally wetting contact angle (i.e. 90°) is found to elevate the transport of the droplet to a higher distance from the substrate relative to a partially wetting case (i.e. 60°). In the lifting removal mechanism, unlike the floating removal mechanism, the particle initial placement is highly critical for the detachment of the merged droplet from the substrate, as well as the elevation of the detached droplet to a longer distance from the substrate. For a partially immersed particle, the critical particle initial position from the substrate above which the droplet-particle system does not jump away from the substrate is independent of particle size and wettability and is about 1.5 rd where rd is the initial size of the droplet.